Inter‐organizational Quality Management: The Use of Contractual Incentives and Monitoring Mechanisms with Outsourced Manufacturing - Handley, Sean M.; Gray, John V. (Production and Operations Management, 2013)
Quality‐related incidents involving contract manufacturers (CMs) are becoming increasingly prevalent. The quality management (QM) literature, however, has focused mostly on QM within a single firm. Thus, the need for data‐driven research on managing quality with outsourced production is evident. We investigate the use and effectiveness of external failure penalties and audits of CMs’ facilities to manage inter‐firm quality. Building on agency theory and extant QM literature, this study addresses two research questions: (i) whether the control mechanisms of quality audits and contractual external quality failure penalties are substitutes or complements in use and (ii) whether they are substitutes or complements in their effectiveness at aligning the quality interests of customers and their CMs. Our analysis uses dyadic data gathered from brand‐owning firms and their CMs representing 95 contract manufacturing relationships in Food and Drug Administration (FDA)‐regulated industries. The results indicate that more severe external failure penalties correspond to a lower use of facility audits (i.e., they are substitutes‐in‐use). We also find that both external failure penalties and facility audits have a unique positive effect on the CM's perception of relative quality importance. Finally, some evidence supports the hypothesis that each mechanism is more effective in the presence of the other (i.e., they are complements‐in‐effectiveness).